Stent graft explantation following endovascular aortic aneurysm repair – a case series - Garcia, Rita Carreira (2022)
INTRODUCTION: Endovascular aneurysm repair (EVAR) offers significant advantages on aneurysm treatment. However, the management of EVAR complications or failure often results in complex surgical approaches, sometimes requiring graft explantation which remains a major challenge and one associated with a high morbidity and mortality. The purpose of this study is to review our contemporary institutional experience with EVAR explantation. METHODS: An institutional administrative database was reviewed to identify patients who were subject of graft explantation following standard infra-renal EVAR between 2011 and 2021. Follow-up was extracted from patient charts. The primary endpoint was perioperative mortality (30-days or in-hospital). Demographics, indications for explantation and procedure details were evaluated. RESULTS: Over a 10-year period, between 2011 and 2021, there were 617 standard primary EVAR procedures performed in our institution for infrarenal aortic aneurysms. During this period, we identified 13 patients submitted to EVAR explantation, two of which were referrals from other vascular centers. All patients were male and mean age at explantation was 71 years (range 47-81). The primary EVAR procedure took place 29 months (range 0-72) before explantation. The primary indication for EVAR was ruptured aortic aneurysm in seven patients. The majority of explantation operations were emergent (6/13, three due to unstable aorto-enteric fistula (AEF), three due to rupture) or urgent (4/13, two stable AEF, two graft infections). In 3 cases, explantation was elective (two type Ia endoleaks and one type II endoleak with sac expansion). None of the patients had been submitted to a previous attempt at endovascular salvage. All patients were submitted to transperitoneal approaches, and all required initial supracoeliac or suprarenal aortic clamping. After explantation, in situ reconstruction was performed in eight patients, six of which with complete EVAR explantation and two with partial EVAR explantation. Two in situ reconstructions were made using superficial femoral veins, and the remaining used prosthetic grafts. Aortic ligation and extra-anatomic bypass were performed in five cases, The 30-day mortality was 54% (seven patients) with 33% of mortality for elective repair, 50% mortality for urgent repair, and 67% mortality for emergent repair. Mean hospital stay after surgery was 48 days for survivors. Mean survival after discharge was 10 months. CONCLUSION: EVAR explantation is still a relatively rare and particularly complex procedure. When the reason for explantation is graft infection and AEF, and when performed in an emergent context, it is a particularly morbid procedure with a dismal prognosis. As the number of endovascular aneurysm repairs increase, our global experience will become increasingly important in bettering our surgical and clinical outcomes.